Gluten- and casein-free dietary intervention for autism spectrum conditions - Whiteley, Paul; Shattock, Paul; Knivsberg, Ann-Mari; Seim, Anders; Reichelt, Karl L.; Todd, Lynda; Carr, Kevin; Hooper, Malcolm (Frontiers in Human Neuroscience, 2013)
Dietary intervention as a tool for maintaining and improving physical health and wellbeing is a widely researched and discussed topic. Speculation that diet may similarly affect mental health and wellbeing particularly in cases of psychiatric and behavioural symptomatology opens up various avenues for potentially improving quality of life. We examine evidence suggestive that a gluten-free, casein-free or combined gluten- and casein-free diet can ameliorate core and peripheral symptoms and improve developmental outcome in some cases of autism spectrum conditions. Although not wholly affirmative, the majority of published studies indicate statistically significant positive changes to symptom presentation following dietary intervention. In particular, changes to areas of communication, attention and hyperactivity are detailed, despite the presence of various methodological shortcomings. Specific characteristics of best- and non-responders to intervention have not been fully elucidated; neither has the precise mode of action for any universal effect outside of known individual cases of food-related co-morbidity. With the publication of controlled medium- and long-term group studies of a gluten- and casein-free diet alongside more consolidated biological findings potentially linked to intervention, the appearance of a possible diet-related autism phenotype seems to be emerging supportive of a positive dietary effect in some cases. Further debate on whether such dietary intervention should form part of best practice guidelines for autism spectrum conditions and onward representative of an autism dietary-sensitive enteropathy is warranted.